The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10584-014-1148-6
|View full text |Cite
|
Sign up to set email alerts
|

Like artificial trees? The effect of framing by natural analogy on public perceptions of geoengineering

Abstract: The linguistic frames used to describe new areas of science and technology can have a powerful effect on the way that those technologies are perceived by the general public. As geoengineering continues to attract scholarly and policy interest, a number of frames have emerged in the scientific, political and media discourse. In the current paper, we provide an empirical test of one of the most prevalent framing devices: describing geoengineering technologies by analogy to natural processes. In an online experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…The direction of the total effect of values is in line with the literature—altruism reduces acceptability (−0.06) and egoism increases acceptability (0.04). Also previously, altruistic values were shown to increase risk perception and decrease acceptability and egoistic values were shown either to have no effect or to increase benefit perception and acceptability …”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The direction of the total effect of values is in line with the literature—altruism reduces acceptability (−0.06) and egoism increases acceptability (0.04). Also previously, altruistic values were shown to increase risk perception and decrease acceptability and egoistic values were shown either to have no effect or to increase benefit perception and acceptability …”
Section: Resultsmentioning
confidence: 67%
“…demonstrated that altruistic and egoistic values and environmental attitudes influence the support of climate policy. Egoistic values also influence the support of climate engineering . De Groot et al .…”
Section: Introductionmentioning
confidence: 99%
“…An additional avenue for future research would be to evaluate potential strategies to increase the acceptance of CCS, such as compensating local residents for specific risks or ensuring and communicating potential local benefits of concrete CCS projects . Moreover, future research could also explicitly focus on bio‐energy with CCS, as it has been shown for climate engineering that describing technologies with natural analogues increases acceptance …”
Section: Discussionmentioning
confidence: 99%
“…Beliefs about naturalness can make technologies, technological products, and environmental interventions more or less acceptable to people (Rozin et al 2004;Gaskell et al 2010;Corner & Pidgeon 2015). Beliefs about unnaturalness are often linked with unfavorable attitudes toward synthetic biology, genetically modified (GM) foods, and genetic engineering more broadly (Shaw 2002;Gaskell et al 2010;Pauwels 2013).…”
Section: Messing-with-nature Beliefsmentioning
confidence: 99%
“…; Gaskell et al. ; Corner & Pidgeon ). Beliefs about unnaturalness are often linked with unfavorable attitudes toward synthetic biology, genetically modified (GM) foods, and genetic engineering more broadly (Shaw ; Gaskell et al.…”
Section: Introductionmentioning
confidence: 99%